Risk Management in The Algerian Insurance Companies –An Empirical Study - LALMI, FATIMA; SLIMANI, ILIES (International Journal of Management, 2015)
The aim of this study is to identify the reality of risk management in the Algerian insurance companies. The results of the survey showed that these companies still suffer from several problems in addition to risk management, such as the use of traditional methods to identify and measure risk, and even the choice of how best to deal unexpected risks.
Keywords: Risk Management, Insurance, Algerian companies to assurrance, Traditional Methods, scientific methods.